Utilization of agricultural waste for the removal of congo red, the environmental pollutant from simulated aqueous solutions - CHOPRA, INDU; NARAYANAN, NEETHU; SINGH, S B (The Indian Journal of Agricultural Sciences, 2021)
Agricultural waste-based adsorbents are becoming attractive choice for the removal of environmental pollutants from water due to their abundance and low cost. Batch adsorption studies were carried out with Parthenium hysterophorus L. (an invasive weed) to explore its potential for the removal of the anionic dye (Congo Red, CR) from simulated aqueous solutions. The experiment was conducted to study the effect of different parameters including contact time, pH (3-10), initial concentration and adsorbent dose on dye removal efficiency of the adsorbent. It was found that using the bioadsorbent, the sorption equilibrium for the dye could be achieved within 45 minutes at lower concentrations. The experimental data was analyzed through Freundlich and Langmuir adsorption isotherms. The data fitted better in Langmuir isotherm (R2=0.975). The results showed that the maximum adsorption capacity (Qm) is 14.49 mgg-1. The results so obtained indicate that the bioadsorbent can be used efficiently for the dye removal.